Assessment of Solid Waste Generation and Cost Benefit Analysis of Operating Solid Waste Management in Madhyabindu Municipality, Nepal - Pokharel, Bibek; Awasthi, Keshab Datt (Journal of UTEC Engineering Management, 2025)
This study conducts a cost-benefit analysis (CBA) of the integrated solid waste management (SWM) system in Madhyabindu Municipality, Nawalparasi (East), focusing on both financial sustainability and operational efficiency. Data were collected from household and institutional surveys, waste measurements, and municipal records, and were compared against Asian Development Bank (ADB) benchmarks. Household waste generation exceeded benchmarks (0.277–0.428 kg/unit/day vs. ADB’s 0.16 kg), indicating inadequate segregation and reduction practices. In contrast, commercial and institutional sectors showed more efficient practices. Offices and hotels revealed inconsistencies, possibly due to change in behavior of waste generation. The three-month theoretical model projected revenue of NPR 2,356,243.82 against costs of NPR 2,409,623.08, with a Benefit-Cost Ratio (BCR) of 0.978 suggesting near sustainability if optimized. However, actual revenue (NPR 922,820) fell short of actual costs (NPR 2,255,046.03), yielding a much lower BCR of 0.409. Major expenditures were linked to recycling (26.50%), transportation (15.24%), and indirect administration (42.42%). No costs were incurred in landfilling due to reliance on pre-existing infrastructure. Revenue was mainly from user fees and compost sales; recyclable sales and fines contributed nothing despite being part of the model. The study concludes that while the system is theoretically sound, improvements in enforcement, source segregation, and recyclable marketing are essential for achieving practical financial viability and scalability.